Leveraging Six Sigma for Enhanced Reliability in Heavy Equipment Operations: Memanfaatkan Six Sigma untuk Meningkatkan Keandalan dalam Operasi Alat Berat - Fahruddin, A'rasy; Araffi, Moh. Faisal (Universitas Muhammadiyah Sidoarjo, 2024)
This study addresses the prevalent issue of mechanical failures in heavy equipment and dump trucks within a leading special steel production firm. Utilizing the Six Sigma methodology, the research conducted in August 2023 aimed to systematically design and implement corrective actions to improve maintenance processes. Preliminary results from the IRGA Department's interventions suggest a significant reduction in breakdown frequency and severity, indicating enhanced operational efficiency and reduced downtime. These findings highlight the potential of Six Sigma as an effective tool in optimizing industrial maintenance strategies, with implications for boosting productivity and sustainability in heavy industries globally. Highlights: Regular maintenance prevents costly damage. Six Sigma ensures systematic improvement. Vision: Leading in quality and environmental care. Keywords: Steel Bar Casting (billet), Flat Bar, Round Bar Production